Combination of LCZ696 and ACEI further improves heart failure and myocardial fibrosis after acute myocardial infarction in mice - Youbin Liu (Biomedicine & Pharmacotherapy, 2021)
Background: LCZ696, an angiotensin receptor–neprilysin inhibitor (ARNi), is reported to play a cardioprotective role after acute myocardial infarction (AMI). Angiotensin-converting enzyme inhibitors(ACEIs) have similar roles. However, it is unclear whether the combination of the two drugs has a better protective effect. The purpose of this study was to investigate the effect of this combination therapy after AMI. Methods: Male C57BL/6 J mice subjected to ligation of left anterior descending artery were treated for 4 weeks with LCZ696, ACEI(benazepril), or both(combination therapy) after induction of MI. Cardiac function, hemodynamics, and inflammatory factors were evaluated at 1 st day, 14th day, and 28th day. Heart weight and myocardial fibrosis were measured at the end of the experiment. Results: Blood pressure was lower in all treatment groups than in the control group. The combination therapy group had the strongest antihypertensive effect. Compared with LCZ696 or benazepril, treatment with combination therapy increased ejection fraction, fractional shortening, and cardiac output and decreased N-terminal pro-B-type natriuretic peptide(NT-proBNP). The ratios of heart weight to body weight in all treatment groups were less than that in the control group. Compared with the control and LCZ696 group, the fibrotic area in the combination therapy group was suppressed and had a lower level of TGF-β1 in the left ventricle. The plasma concentration of bradykinin and renin in the combination therapy group were highest among groups at 14th and 28th day. Conclusions: LCZ696 in combination with benazepril showed better positive effects in modulating heart failure and myocardial fibrosis after acute AMI in mice and affect some inflammatory markers.